LOGISTICS PRINCIPLES IN LOGISTICS SUPPORT PLAN - Eddy S. Harisanto (JURNAL TEKNOLOGI INDUSTRI, 2012)
Logistics in an art and a science. The science aspect enables logisticians to accomplish their mission methodically, logistics can not be separated from Strategy and tactics. In addition, people may study logistics like a systemized knowledge. In practice the limitations are always there.  Principles is a comprehensive and Fundamental doctrine or assumption. Therefore logisticians must understand and apply logistics Principles in  managing logistics support, Logistics principles has eight principles those are : Logistics Intelligence, Objective, Generative logistics, Interdependence Simplicity, Timeliness, Forward Impetus and Security.  Beside logistics principles,  logisticians need to know about the logistics support plan to.  Paragraphs of Material and Services To determine these point, Logistics staff has to know how well the terrains. Logistics principles that must be used in every logistic support plan it doesn’t matter in small or huge operations.  Logistics support plans are based on designed to support the combat operation. However, because of constraints of time, space and resources, the use of logistics principles and tactical requirement must be balanced. The mission of combat operation and also the objective of Logistics support operation  determine  how logistics support will be accomplished. As also, you know in what weather the operation will be, you can determine the equipment required easily also easily understands of transportation, Material and Service.  Although services do not influence directly to the combat power, but services plan must not be ignored. So Logistics Intelligence, Objective, Generative logistics, Interdependence, Simplicity, Timeliness/Accuracy, Forward impetus, Cost Effectiveness and Security are logistics principles that must be used in every logistic support plan. Keyword  :  Logistic, Support Plan, Intelligence